Pengaruh Risiko Pasar dan Nilai Tukar Rupiah Terhadap Return Saham - Dyna Octavia Suryono Putri; Meta Nursita (Economic Reviews Journal, 2025)
This study aims to find out and obtain empirical evidence of the influence of market risk and the rupiah exchange rate on stock returns. This type of research is quantitative with a research population in non-cycical customer companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The number of samples used amounted to 230 data from 46 non -cycrical customer sector companies obtained using purposive sampling based on predetermined criteria. Hypothesis testing using panel data regression using EViews 12. The results show that, Market risk has a significant effect on stock returns, Meanwhile, the rupiah exchange rate influence has no significant effect on stock returns.